Anxiety and Executive Functions: Results from a Neuropsychological Battery and a Self-report Questionnaire - Romero-Méndez, Christian Alexis (2025)
In Mexico, a high percentage of young people experience symptoms of generalized anxiety, which are associated with difficulties in executive functions (EF). However, previous studies have shown inconsistent results, as they often rely solely on either objective or subjective measures. Therefore, this study focused on analyzing the relationship between generalized anxiety and EF using both a neuropsychological battery and a self-report questionnaire, in order to provide a more comprehensive understanding of cognitive functioning in adolescents. A quantitative, non-experimental, cross-sectional, correlational, and explanatory design was employed. The sample consisted of 96 adolescents between 12 and 15 years old from the state of Puebla, Mexico. A total of 10.41% of participants presented severe symptoms of generalized anxiety. A significant relationship was found between anxiety and one of the neuropsychological tests, the consecutive subtraction task (100-7), which assesses working memory (ß = -.244, p = .017). In contrast, all EFs assessed through self-report showed significant associations with anxiety, particularly emotional control (ß = .696, p = .001) and inhibition (ß = .638, p = .001). The discrepancy between self-report and neuropsychological test results suggests that questionnaires capture the subjective perception of cognitive difficulties influenced by emotional factors, whereas neuropsychological tests measure objective performance. These findings highlight the importance of combining both types of measures, as they provide complementary perspectives that allow for a more accurate and ecologically valid assessment of EF in individuals with anxiety.